2016
DOI: 10.1016/j.humpath.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CEA, CA19-9, CA125, and EpCAM in pseudomyxoma peritonei

Abstract: Pseudomyxoma peritonei is a fatal clinical syndrome with mucinous tumor cells disseminated into peritoneal cavity and secreting abundant mucinous ascites. The serum tumor markers CEA, CA19-9, and CA125 are used to monitor pseudomyxoma peritonei remission, but their expression at tissue level has not been well characterized. Herein, we analyzed expression of these proteins and the adenocarcinoma marker EpCAM in 92 appendix-derived pseudomyxoma peritonei tumors by immunohistochemistry. All tumors were found to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
1
20
0
5
Order By: Relevance
“…However, CA19 -9 cannot be used in patients whose FUT3 is mutated (47,48), because other FUT enzymes do not compensate for the lack of ␣1,4-fucosylation activity of this enzyme. In our previous study, we demonstrated that 9% (8/92) of PMP cases showed impaired CA19 -9 expression because of FUT3 mutation (26). In our present study, we found that all these cases showed intense staining of sLe x , which can be synthesized by FUT 3-7 enzymes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, CA19 -9 cannot be used in patients whose FUT3 is mutated (47,48), because other FUT enzymes do not compensate for the lack of ␣1,4-fucosylation activity of this enzyme. In our previous study, we demonstrated that 9% (8/92) of PMP cases showed impaired CA19 -9 expression because of FUT3 mutation (26). In our present study, we found that all these cases showed intense staining of sLe x , which can be synthesized by FUT 3-7 enzymes.…”
Section: Discussionsupporting
confidence: 58%
“…The patients received no preoperative oncological treatments. To avoid fucosyltransferase 3 (FUT3) mutated cases, occurring in 5-10% of the population, only CA19 -9 immunopositive cases were included based on our previous study (26). All tissue specimens were routinely fixed and embedded in paraffin at the Department of Pathology, HUSLAB, Helsinki University Hospital, between 2007 and 2016, and the study was approved by the Ethics Committee of the Helsinki University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Pirjo Nummela et al found that pseudomyxoma peritonei tumour cells invariably express CEA and EpCAM. These authors propose that CEA and EpCAM could be exploited to develop targeted therapies against this malignancy [55]. Immunohistochemistry can aid in the diagnosis of PMP based on the following features: CK7 (+), CK20 (+), CDX2 (+), MUC2 (+), MUC5AC (+), ER (−) and PR (−) [5659].…”
Section: Discussionmentioning
confidence: 99%
“…Some tumor markers have been documented to be valuable in the management of PMP – CEA, CA19.9, and CA125 – albeit these are relatively aspecific 17. Elevated levels of tumor markers indicate more aggressive disease, with increased risk of recurrence, progression, and poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%